DESCRIPTION OF MOTHER'S LEVEL OF KNOWLEDGE ABOUT PLAY ACTIVITIES IN PRESCHOOL AGE CHILDREN TREATED IN THE CHILDREN'S ROOM - Aulia Asman, Liza; Hidayati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2021)
Playing is activity could not separate from life child’s whose pain and be care in hospital. When the children was brought to the hospital meet the doctor, nurse and hearting medical action, this situation make the child’s worry. Worry cause of children is different, especially preschool, injury and pain cause of hearting procedure will worry cause. To minimization worried to use effective nursing planning, one of them is requirement play in hospital. Playing in hospital is parent responsibility and nurse of pediatric word. The children feel comfort and free to expression that feeling if playing accompany by parent. The important of Involvement parent, that common knowledge of patent about playing preschool. The purpose of this research are to find out descriptive of stage mother’s knowledge about activity playing to child preschool who be care on pediatric word. This research used descriptive methodology design that do to mothers have preschool on pediatric word general district Hospital. The populations are 17 mothers’ has preschool child who be care on pediatric word of general district hospital Padang Pariaman and technical sampling with method total sampling. Data analyses are used statistic univariat. This research result obtain knowledge stage mothers is enough (56,45%) For that need the existence policy of hospital institution of pediatric, to add knowledge of mothers about important playing activity pediatric word and conducted playing activity to children has and do playing activity to child who be care on pediatric words.